SMEs performance in Malaysia: the role of contextual ambidexterity in innovation culture and performance - Ramdan, Mohamad Rohieszan; Abd Aziz, Nurul Ashykin; Abdullah, Nor Liza; Samsudin, Norsamsinar; Veer Singh, Gurcharanjit Singh; Zakaria, Thuraiya; Mohd Fuzi, Nursyazwani; Ong, Sharon Yong Yee (Multidisciplinary Digital Publishing Institute, 2022)
Small and medium-sized enterprises (SMEs) in both the industrial and service sectors have been identified as the drivers of Malaysia’s fast economic growth. However, SMEs are faced with an inherent issue of lack of resources and capabilities which constrains the ability of SMEs to improve performance. Due to this, it is critical for SMEs to understand and develop an important capability that supports them in facing a dynamic and competitive business environment. This study examines the mediating role of contextual ambidexterity as a dynamic capability in the relationship between innovation culture and SME performance. The online surveys were carried out starting from 5th July until 25th July 2021. A total of 277 SMEs in Selangor, Malaysia participated in this study and Covariance-Based Structural Equation modeling analysis was utilized to test the hypotheses. The findings show that in terms of direct relationships, innovation culture has a significant positive relationship with contextual ambidexterity, while innovation culture and contextual ambidexterity have a significant positive relationship with SME performance. The findings showed that contextual ambidexterity is significant as a mediator in the relationship between innovation culture and SME performance. This study makes an important contribution to the management field by highlighting the role of contextual ambidexterity, which is often the focus of large companies. These findings support the notion of dynamic capability that accentuates the importance of developing capabilities in dealing with dynamic and challenging situations.